Hubungan pendidikan, pengetahuan, pola asuh ibu, dan ketahanan pangan rumah tangga dengan kejadian stunting pada balita 24-59 bulan - Firda Santosa; Fitria Fitria; Anna Fitriani (UHAMKA PRESS, 2026)
The problem of stunting can be caused by maternal factors such as education level, knowledge, and parenting patterns as well as food security of a household which has an impact on the availability of food ingredients and food intake. The purpose of this study was to determine the Relationship between Level of Education, Knowledge, Maternal Parenting and Household Food Security with the Incidence of Stunting in Toddlers 24-59 Months in Serang Baru District. This research is an observational study that uses a quantitative approach with a cross-sectional study design. The sample used was 104 mothers who had toddlers aged 24-59 months in Serang Baru District. The sampling technique for the research location was purposive, then cluster random sampling to minimize the coverage of the research area to the village level and accidental sampling for available samples according to the inclusion criteria. Data were taken related to the level of maternal education, maternal knowledge, maternal parenting and household food security through questionnaires and the incidence of stunting in toddlers aged 24-59 months obtained from the results of measuring height using a microtoise. The results of statistical tests showed that there was a relationship between education level, knowledge, maternal parenting and household food security (p<0.01) with the incidence of stunting in children (24-59 months) in Serang Baru District.